Sustained type 1 diabetes self‐management: Specifying the behaviours involved and their influences. Issue 5 (8th December 2020) - Hamilton, K.; Stanton‐Fay, S. H.; Chadwick, P. M.; Lorencatto, F.; de Zoysa, N.; Gianfrancesco, C.; Taylor, C.; Coates, E.; Breckenridge, J. P.; Cooke, D.; Heller, S. R.; Michie, S.; et al.
Abstract: Aims: Sustained engagement in type 1 diabetes self‐management behaviours is a critical element in achieving improvements in glycated haemoglobin (HbA1c) and minimising risk of complications. Evaluations of self‐management programmes, such as Dose Adjustment for Normal Eating (DAFNE), typically find that initial improvements are rarely sustained beyond 12 months. This study identified behaviours involved in sustained type 1 diabetes self‐management, their influences and relationships to each other. Methods: A mixed‐methods study was conducted following the first two steps of the Behaviour Change Wheel framework. First, an expert stakeholder consultation identified behaviours involved in self‐management of type 1 diabetes. Second, three evidence sources (systematic review, healthcare provider‐generated 'red flags' and participant‐generated 'frequently asked questions') were analysed to identify and synthesise modifiable barriers and enablers to sustained self‐management. These were characterised according to the Capability‐Opportunity‐Motivation‐Behaviour (COM‐B) model. Results: 150 distinct behaviours were identified and organised into three self‐regulatory behavioural cycles, reflecting different temporal and situational aspects of diabetes self‐management: Routine (e.g. checking blood glucose), Reactive (e.g. treating hypoglycaemia) and Reflective (e.g. reviewing blood glucose data to identify patterns). Thirty‐four barriers and five enablers were identified: 10 relating to Capability, 20 to Opportunity and nine to Motivation. Conclusions: Multiple behaviours within three self‐management cycles are involved in sustained type 1 diabetes self‐management. There are a wide range of barriers and enablers that should be addressed to support self‐management behaviours and improve clinical outcomes. The present study provides an evidence base for refining and developing type 1 diabetes self‐management programmes.